DINAMIKA KOMUNIKASI BISNIS INDONESIA DAN TIONGKOK DALAM PERSPEKTIF UNCERTAINTY AVOIDANCE DAN LONG TERM ORIENTATION: STUDI PUSTAKA BERBASIS TEORI HOFSTEDE - Laurentius Gustiemas Erlangga Putra; M. Hafidz Arif Gumilang; Resha Fadhillah (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
National cultural differences influence the effectiveness of cross-border business communication. This article analyzes the implications of Uncertainty Avoidance and Long-Term Orientation on business communication patterns between Indonesia and China. Using a literature review approach, this study examines Hofstede’s cultural dimension scores, academic journals, and relevant literature. The findings indicate that differences in tolerance for uncertainty and Long-Term Orientation affect decision-making, conflict management, and professional relationship building. This study contributes theoretically by extending the application of Hofstede’s cultural dimensions through a focused analysis of Uncertainty Avoidance and Long-Term Orientation, which have received limited attention in previous studies on Indonesia–China business communication.